STRATEGY FOR DEVELOPING THE POTENTIAL TOURISM OF MASSENREMPULU BOTANICAL GARDEN IN INCREASING THE INTEREST OF TOURISTS IN BATU MILA VILLAGE, MAIWA DISTRICT, ENREKANG REGENCY - Sari, Novita; Sakawati, Herlina; Aslinda, Andi (Jurnal Aktor, 2025)
This research aims to look at the potential development strategy for the Massenrempulu Botanical Garden tourist attraction in increasing tourist interest in Enrekang Regency. The type of research used is a qualitative method with a descriptive approach. From the research results, there are four indicators, namely: First, environmental analysis, the management of the Massenrempulu Botanical Gardens uses Strategic Management analysis in organizing tourist attraction programs through the formation of a strong work structure and experts in their respective fields. Meanwhile, for external matters, coordination with various SKPDs in Enrekang district and the private sector is to continue to build programs that are synergistic by prioritizing attractions according to the needs of tourists. Second, strategy formulation, Upt Kebun Raya Massenrempulu in preparing sustainable programs always pays attention to the needs and demands of tourists, so that improvements in service quality continue to be carried out by trying to create programs that can meet tourist needs. Third, implementation of strategies, patterns of implementation of activities carried out by the Massenrempulu Botanical Gardens Center, which always innovates and improves existing attractions at tourist attractions. Apart from that, additional tourist attractions were also carried out to increase visitor interest. Fourth, evaluation and control, all the Massenrempulu Botanical Garden Upt programs that have been implemented have been running effectively, but there are still several obstacles in the process of maintaining tourist attractions due to the lack of capital available